2018
DOI: 10.1111/vsu.13105
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of surgical site infection on survival after limb amputation in the curative‐intent treatment of canine appendicular osteosarcoma: a Veterinary Society of Surgical Oncology retrospective study

Abstract: Objective To determine the influence of surgical site infection (SSI) on the median disease‐free interval (DFI) and median survival time (MST) in dogs after amputation in the curative‐intent treatment of appendicular osteosarcoma (OSA). Study design Multi‐institutional retrospective cohort study. Animals Fifteen dogs with OSA and SSI, and 134 dogs with OSA and no SSI. Methods Medical records were reviewed, and dogs were included if the following criteria were met: histologic confirmation of OSA, no evidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…1,2,6,16 A recent report found that SSI in dogs that undergo primary amputation for definitive local control of OSA does not carry a similar survival benefit. 17 In the aforementioned study, the SSI risk was 10%, with a similar ratio of superficial and deep infections and all SSI were resolved within 30 days. A possible difference between these two groups of dogs is the chronicity and severity of infection.…”
Section: Statistical Evaluationmentioning
confidence: 73%
See 3 more Smart Citations
“…1,2,6,16 A recent report found that SSI in dogs that undergo primary amputation for definitive local control of OSA does not carry a similar survival benefit. 17 In the aforementioned study, the SSI risk was 10%, with a similar ratio of superficial and deep infections and all SSI were resolved within 30 days. A possible difference between these two groups of dogs is the chronicity and severity of infection.…”
Section: Statistical Evaluationmentioning
confidence: 73%
“…Our finding of prolonged survival with SSI in dogs that undergo limb salvage surgery for appendicular OSA has been consistently reported in the veterinary literature . A recent report found that SSI in dogs that undergo primary amputation for definitive local control of OSA does not carry a similar survival benefit . In the aforementioned study, the SSI risk was 10%, with a similar ratio of superficial and deep infections and all SSI were resolved within 30 days.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Before the 1970s, amputation was the main treatment for OS 4 . However, early metastasis may have occurred before amputation such that patients cannot be cured completely 5 . Indeed, the overall therapeutic effects remains poor 6 .…”
Section: Introductionmentioning
confidence: 99%